Students with hearing impairment and Chemistry teaching: mapping academic production in SIMPEQUIs (2006-2021) (Research, Society and Development, 2021)
This research is the result of meetings given for the Undergraduate Course in Natural Sciences involving themes related to Chemistry Teaching and Inclusive Education, with emphasis on Hearing Impairment. The objective of this research was to map the works published in SIMPEQUIs between 2006 and 2021. The research was bibliographical in nature and sought to demonstrate to undergraduates the issue of inclusion of students with limitations and who will cross the path of their professional history. The methodology used was the reading of the records published in the chosen event, based on published works with this theme and discussions carried out during the Chemistry Teaching process. Our results were categorized into five parts: Conceptions of chemistry teachers and students; Use of symbology using LIBRAS, Theoretical works with reference to the State of the Art; Experimentation and Teacher Training. We conclude that there are important factors that significantly interfere in the association, learning and inclusion of students with Hearing Impairment in Chemistry classes: 1- Request for a LIBRAS Interpreter; 2- Materials necessary for the deaf student to develop reading and writing skills; 3- Classroom equipment, with visual resources; 4- The importance of inclusive education in the initial training of graduates and the search for continued training by Chemistry teachers in relation to the object of study of this research; 5- Preparation of low-cost materials by the students themselves, in order to value and motivate the class in general.